Design and Construction of a Novel Flame-Based Electroanalyzer for Sensitive and Selective Detection of Alkali ions at nM Levels by Amperometry: Discrimination of Alzheimer's Disease. (1st September 2016) - Doroodmand, Mohammad Mahdi; Ghasemi, Fatemeh
Graphical abstract: Highlights: Flame-Based Electroanalyzer. Discrimination of Alzheimer's disease. Ultra-trace Alkali Detection. Abstract: A novel and sensitive detection system was introduced based on amperometry inside flame for rapid determination of total alkali ions in the human cerebrospinal fluids (CSFs) at nM levels. For this purpose, a triangular (Y-shaped) three-electrode system included two stainless steel rods as well as a brass disk as working, counter and pseudo reference electrodes inside H2 /air flame. In the fabricated system, mixture of H2 and air was introduced to the flame through a capillary hole along the working electrode. The analyte was introduced to the flame as electrolyte through the formation of aerosols using a sonicator and N2 as carrier gas. The inter-electrode distance was set to 2.0 mm. Based on one at a time method, the optimum flow rates of H2, air and N2 were 375, 259 and 2.6 mL min -1, respectively. Solution of HCl (0.45 M) was also selected as supporting electrolyte. Maximum sensitivity (peak current) was observed at DC potential of −36.0 ± 1.0 V (vs. the pseudo reference electrode). According to the figures of merit under the optimized condition, this system had linear dynamic ranges between 250-12000 ng mL -1 for Li+, 180–11400 ng mL -1 for Na +, 200–12000 ng mL -1 for K + and 110–6400 ng mL -1 for Cs + . Relative standard deviation (RSD) for 8 replicate analyses of Na+ as selected model was ∼7.0%. Based on 90% of maximum response (t90), the response time was estimated to be 3.0 s. No interference was observed, when introducing at least 1000-fold excess of foreign species such as Ag +, Ni 2+, Mg 2+, Zn 2+, Fe 3 +, NH4 +, acetone, ethanol, CH3COO -, NO3 -, Cl -, oxalate, SO4 -2, tartrate, and PO4 -3 . However ∼20% positive error was observed during introduction of ∼500-fold excess of some alkaline earth metal cations such as Ba 2+ and Ca 2+ . The validity of this method was evaluated via analyses of different water samples. The reliability and application of this method was finally evaluated via determination of total alkali ions in different CSFs. Good correlation was observed between the total concentrations of alkali ions and Alzheimer's disease (AD) in various patients. This method was therefore applicable for discrimination and prediction of AD via analyses of alkali species in the CSFs.